Research of Vibration Characteristics of Gear-rotor-bearing System with Compound Faults - Haisheng Feng; Yongqiang Xiao; Baoguo Wu; Jin Dang; Jianping Wang; Fengtao Wang (Jixie chuandong)
For the vibration response of gear-rotor-bearing system with compound faults，after the gear pair model and ball bearing model are combined，a coupling vibration model of gear-rotor-bearing system with 36 degrees of freedom based on the Lagrange equation is built，and the spalling defect on the driving gear and surface damage compound faults of bearings are set to study the vibration response of gear pair under compound faults. The results show that the vibration amplitude of the healthy gearing-rotor-bearing system is relatively uniform on time domain，and the vibration spectrum mainly consists of the characteristic frequencies of the bearing outer raceway，as well as the meshing frequencies of the gear pair. When there is a spalling single fault on the gear pair，the sidebands generated by the frequency modulation of the rotating shaft and meshing frequencies can be found. When compound faults of the gear-rotor-bearing system occurs，the amplitude of system vibration on the time domain increase and the vibration are becoming more complicated. The modulation phenomenon is serious on frequency domain， and the amptitude of the signal generated by modulation increases. However，the fault frequencies and harmonic frequencies can be found in the vibration frequency domain，which can determine fault types of system.